Arginine Vasopressin Alters Both Spontaneous and Phase-Locked Synaptic Inputs to Airway Vagal Preganglionic Neuron via Activation of V1a Receptor: Insights into Stress-Related Airway Vagal Excitation - Yan, Xianxia; Chen, Xingxin; Guo, Yuhong; He, Ding; Chen, Yonghua; Xia, Chunmei; Wang, Jijiang (Frontiers in Cellular Neuroscience, 2017)
The airway vagal preganglionic neurons (AVPNs) in the external formation of the nucleus ambiguus (eNA) play a major role in the vagal control of tracheobronchial smooth muscle tone and maintenance of airway resistance. The eNA receives vasopressinergic projection from the hypothalamic paraventricular nucleus, the key node for the genesis of psychological stress. Since airway vagal excitation is reportedly to be associated with the psychological stress-induced/exacerbated airway hyperresponsiveness in asthmatics, arginine vasopressin (AVP) might be involved in stress-related airway vagal excitation. However, this possibility has not been validated. This study aimed to test whether and how AVP regulates AVPNs. In rhythmically active medullary slices of newborn rats, retrogradely labeled AVPNs were identified as inspiratory-activated and inspiratory-inhibited AVPNs (IA- and II-AVPNs) using patch-clamp techniques according to their inspiratory-related firing behavior and synaptic activities. The results show that under current clamp, AVP depolarized both IA- and II-AVPNs, and significantly increased their spontaneous firing rate. Under voltage clamp, AVP elicited a slow inward current, and significantly increased the frequency of spontaneous excitatory postsynaptic currents in both types of AVPNs. In addition, AVP significantly enhanced the phase-locked excitatory inspiratory inward current in IA-AVPNs, but significantly suppressed the phase-locked inhibitory inspiratory outward current in II-AVPNs. In both types AVPNs, AVP significantly increased the frequency and amplitude of pharmacologically isolated spontaneous GABAergic and glycinergic inhibitory postsynaptic currents. All of the AVP-induced effects were prevented by SR49059, an antagonist of V1a receptors, but unaffected by SSR149415, an antagonist of V1b receptors. AVP did not cause significant changes in the miniature excitatory postsynaptic currents, miniature inhibitory postsynaptic currents and membrane input resistance of either type of AVPNs. These results demonstrate that AVP, via activation of V1a receptors, enhanced the spontaneous excitatory and inhibitory inputs similarly in the two types of AVPNs, but differentially altered their phase-locked inspiratory excitatory and inhibitory inputs. The overall effects of AVP are excitatory in both types AVPNs. These results suggest that increased central AVP release may be involved in the stress-induced augmentation of airway vagal activity, and, consequently, the induction or exacerbation of some airway diseases.